Design of a smart photovoltaic greenhouse with plant growth based Monitoring System - Islam, MD Jubydul; Raj, MD Naser; Bhuiyan, MD Shahrear; Esha, Sazia Khandoker (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.